Short-Interval Self-Learning to Improve Retention of Resuscitation Skills: A Randomized Controlled Trial (International Journal of First Aid Education)
The optimal interval and methods for cardiopulmonary resuscitation (CPR) retraining remain unclear. We evaluated the difference in CPR skills one year after a 45-minute chest compression-only CPR training among participants receiving short self-learning refresher training at 3-month intervals, those receiving this training at 6-month intervals, and those without the refresher training. Participants were randomly assigned to the 3-month group, 6-month group, or control group. Resuscitation skills were assessed immediately after the initial training, and at 1 year after the training. The primary endpoint was the number of chest compressions performed with appropriate depth one year after the training. Among 129 participants that were selected, 112 were fully evaluated. Although no significant differences were found in the baseline characteristics among the three groups, the self-training groups demonstrated a tendency to perform fewer chest compressions with appropriate depth (p = .122). No significant differences were observed between the three groups in terms of the number of chest compressions with appropriate depth one year after the training (p = .895). However, the appropriate number of chest compressions, the number of chest compressions with appropriate depth, and chest compression depth in the short-interval self-retraining groups one year later were better than those observed immediately after training. Short self-retraining every 3 or 6 months after the chest compression-only CPR training could not be attributed to the retention of chest compression skills with appropriate depth. However, short, frequent self-retraining in persons with poor skills might be useful in acquiring chest compression skills.